2006
DOI: 10.1021/es060075o
|View full text |Cite
|
Sign up to set email alerts
|

Considering User Attitude in Early Development of Environmentally Friendly Technology:  A Case Study of NoMix Toilets

Abstract: Urine source separation (NoMix technology) has been proposed as a sustainable alternative to centralized wastewater treatment systems. Radical changes necessitate an early inclusion of sociological expertise, thus offering a real chance for transdisciplinary collaboration. The practical aim of our survey is to find out how users accept and use existing NoMix toilets and how this could be encouraged. We collected 1249 questionnaires from 2002 to 2004 in one Swiss school and one Swiss research institute. The tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 33 publications
(52 reference statements)
3
39
1
1
Order By: Relevance
“…Another explanation could be that this concept is very new for the study area, and it always takes time to accept new ideas. As Lienert and Larsen (2006) showed that the discussion is more effective than only giving information about eco-toilet, but unfortunately we could not make long discussion with the participants in this study.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Another explanation could be that this concept is very new for the study area, and it always takes time to accept new ideas. As Lienert and Larsen (2006) showed that the discussion is more effective than only giving information about eco-toilet, but unfortunately we could not make long discussion with the participants in this study.…”
Section: Discussionmentioning
confidence: 76%
“…The eco-toilet was explained as a simple and a cheap model, which might make majority of the participants to be interested as Medilanski et al (2006) present that 79% people preferred to use cheap dry-toilet rather than the expensive No-Mix toilet. Our result showed that the people who were aware about urine fertilizer, however, were not interested to use urine fertilizer in home plots, and therefore it seems to be important to discuss and convince the people about this idea as presented by Lienert and Larsen (2006). However, the situation seems to be different in Nepal because many farmers who did not know about urine fertilizer were interested to use urine fertilizer as this might be due to needing of fertilizer and similar opinion presented by Manandhar et al (2004).…”
Section: Discussionmentioning
confidence: 84%
“…Many communities in Western Europe and the United States are faced with an aging wastewater treatment infrastructure, while also experiencing growth and development. This situation makes long-term planning and the definition of priorities much more demanding than in the past (16). Despite some remaining uncertainties in our analysis (see Supporting Information), we believe the application of MCDA helps to clarify the role that peak-shaving can play in allowing these communities to postpone or avoid expensive WWTP expansions.…”
Section: Discussionmentioning
confidence: 96%
“…Em outra pesquisa, também na Suíça, feita por Lienert;Larsen (2006), realizada em prédios públicos (faculdade, instituto de pesquisa e uma biblioteca) que dispõem de sanitários separadores, os níveis de aceitação foram extremamente satisfatórios. De um total de 1.249 entrevistados da faculdade e do instituto de pesquisa, 72% afirmaram que essa tecnologia é uma boa ideia.…”
Section: Satisfação Quanto à Infraestrutura E Percepção Do Ecossaneamunclassified